Community Perception of Local Public Transportation (Angkot) Performance in Palu, Indonesia - Haycal, Digho Dovano; Rifai, Andri Irfan; Thole, Joko (Citizen : Jurnal Ilmiah Multidisiplin Indonesia, 2022)
The high population growth rate in the world has increased the need for the transportation sector. The people of Palu city use public transportation modes rather than private modes of transportation. These impacts increase the growth particularly relevant to the transportation sector resulting in human dependence on fossil fuels, global warming, poverty, and social inequality. This paper aims to determine the community's level of importance and satisfaction with local transportation (Angkot) in Palu City. It is hoped that it can help the interest of the people of Palu City in using city transportation. The method used in this paper is Importance-Performance analysis with Microsoft Excel. Based on the results of the analysis. There are five essential variables whose performance must be improved, then nine critical variables that align with expectations so that these variables must improve, and two parameters that are not important but have an above-average performance level.